Transient Electromagnetic Field Coupling to Buried Thin Wire Configurations: Antenna Model versus Transmission Line Approach in the Time Domain - Dragan Poljak; Silvestar Šesnić; Khalil El-Khamlichi Drissi; Kamal Kerroum; Sergey Tkachenko (International Journal of Antennas and Propagation)
The paper examines the antenna model for the transient analysis of electromagnetic field coupling to straight wire configurations buried in a lossy half-space. The wire antenna theory (AT) model is implemented directly in the time domain and it is based on the corresponding space-time Pocklington integrodifferential equation. The solution of the Pocklington equation is carried out analytically. The obtained results are compared against the results calculated via the transmission line (TL) approach. The TL approach is based on the telegrapher’s equations, which are solved using the modified transmission line method (MTLM) and Finite Difference Time Domain (FDTD) technique, respectively. Some illustrative computational examples for buried straight wire scatterer and horizontal grounding electrode are given throughout this work.